The Impact of Private Label Introduction on Assortment, Prices, and Profits of Retailers - Meilin Ma; Ralph Siebert (Center for Economic Studies and ifo Institute (CESifo), 2021)
We study how the introduction of private-label brands (PLs) affects retailers' prices, demand, and profits, explicitly accounting for assortment adjustments of national brands (NBs) in retail stores. Using a detailed dataset on the U.S. beef market, we find that, when PLs are added to the low-priced market segment, stores reposition NBs to further differentiate them from the PL and remove NBs from the same market segment. However, if PLs are introduced into the high-priced segment, NBs are not repositioned or removed from the same segment; this way, the store can compete with other stores in product variety. PL introduction and PL-driven assortment changes of NBs impose a small effect on NB prices. In contrast, PLs strongly cannibalize NB demand, and the assortment changes help steer consumers toward PLs, which imposes large negative effects on NB demands and increases store-level profits.
Keywords: D22; L66; L81; 330; prices and demand of national brands; private label; retailer assortment decisions